THE IMPLEMENTATION OF FLIPPED CLASSROOM IN EFL CLASS: A TAIWAN CASE STUDY - Havwini, Tian; Wu, Yi-Ting (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2019)
This article reports on a case study designed to examine the implementation of flipped classroom in the EFL classroom in Taiwan. In addition, students’ perception of flipped classroom was also investigated. Sixty-one senior high school students participated in this study; data were gathered from students’ English midterm exam score and questionnaire. The data then were quantitatively analyzed by using T-test and descriptive statistics. The results show that students’ English proficiency in flipped classroom was not significantly different with students in traditional classroom. However, the results reveal that students’ perception of flipped classroom were generally favorable. Students’ contended that flipped classroom enhanced their motivation in learning English, as they liked the self-pace through the course and they stated that flipped classroom gave them more class time to practice English. The results presented here may facilitate improvements in the implementation of flipped classroom in EFL class. Furthermore, suggestions for further research are also presented.